Prevalence of Lung Lesions at Autopsy: A Histopathological Study - Khare, Pratima (J Clin Diagn Res, 2017)
INTRODUCTION: Autopsies are carried out to establish the identity, cause of death, time of death, and ante-mortem or post-mortem nature of death. These help in establishing the cause of death and ascertain the disease process which led to death. AIM: To study the prevalence and pattern of lung diseases in medicolegal autopsies, confirmed by histopathological examination. MATERIALS AND METHODS: This retrospective study was carried out in the Department of Pathology. Tissue bits from lungs, retrieved at the time of autopsy, were preserved in 10% formalin. These were processed and examined microscopically. A total of 86 cases were received during the period of study. RESULTS: Among these 86 cases, in 4 cases (4.8%) the tissue was autolysed and in another 26 cases (30.1%) histopathology was unremarkable. Significant microscopic findings were found in 56 cases (65.1%). Wide spectrum of microscopic findings were seen, the commonest being oedema and congestion (28.5%) followed by changes in interstitium (11.9%). There were 9.5% cases of granulomatous inflammation and 5.9% cases each of acute pneumonia and emphysema. There were 1.2% cases each of Hyaline Membrane Disease (HMD), Meconium Aspiration Syndrome (MAS) and Acute Respiratory Distress Syndrome (ARDS) in the series. The series also had 1.2% cases of young adult having fungal colonies surrounded by necrosis and abscess formation. Possibility of mucormycosis was suggested in that case. CONCLUSION: This study highlights various lesions in lungs confirmed by histopathology, which were either incidental or direct cause of death. The short coming in present study was non receipt of whole organ or representative sample at the time of autopsy, which if overcome will set much higher standard of autopsy reporting and would be a more useful tool in understanding cause of death.